التمكين كمدخل استراتيجي لتحقيق التميز في الأداء لدى أعضاء هيئة التدريس من وجهة نظر رؤساء الأقسام : دراسة على عينة من جامعات الشرق الجزائري - صوام، راضية Swam,Radia (جامعة عمار ثليجي بالأغواط, 2017)
هدفت الدراسة إلى التعرف على تأثير التمكين الإداري في تميز الأداء الوظيفي لدى أعضاء هيئة التدريس في بعض مؤسسات التعليم العالي في منطقة الشرق الجزائري. ولتحقيق أهداف الدراسة تم تصميم وتطوير استمارة، وزعت على 65 رئيس قسم في المؤسسات محل الدراسة. وقد توصلت الدراسة إلى النتائج الآتية: - مستوى التمكين الإداري لدى القيادات الأكاديمية كان مرتفعا في المؤسسات محل الدراسة، كما أن مستوى الأداء لدى أعضاء هيئاتها التدريسية كان مرتفعا أيضا. - يوجد أثر ذو دلالة إحصائية للتمكين الإداري في تميز الأداء الوظيفي لأعضاء هيئة التدريس في المؤسسات محل الدراسة. كما أوصت الدراسة بضرورة توفير مناخ صحي للعمل في المنظمات محل الدراسة، يسمح بتطبيق مفهوم التمكين عمليا وعقائديا.
The study aimed at identifying the impact of the administrative empowerment on distinguishing the functionality of the faculty teaching members in some of the higher education institutions in the East Algerian region. And in order to achieve the objectives of the study a well developed form was designed, and then distributed to 65 head of department in the institutions under study. The study got the following results: - The level of the administrative empowerment among the academic leaders was high in the institutions of the study, and the level of performance of the faculty teaching members was also high. - There is a statistically significant effect of the administrative empowerment characterizing the functioning performance of the faculty teaching members of institutions under study. - The study also recommended for the need to provide a healthy environment of work in organizations under study, and which allows applying the concept of empowerment practically and ideologically.
Keywords: الجزائر -- مؤسسات التعليم العالي -- هيئة التدريس -- التمكين الإداري -- إدارة الجامعات